2005
DOI: 10.1016/j.jpainsymman.2005.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Factors Predicting Home Death for Terminally Ill Cancer Patients Receiving Hospital-Based Home Care: The Lyon Comprehensive Cancer Center Experience

Abstract: This study aimed to determine factors favoring home death for cancer patients in a context of coordinated home care. A retrospective study was conducted among patients followed up by the home care coordinating unit of the cancer center of Lyon. The main endpoint was place of death. Univariate analysis included general characteristics (age, gender, rural or urban residence, disease), Karnofsky Index (KI), type of care at referral (chemotherapy, palliative care, or other supportive care), and coordinating medica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 36 publications
4
14
0
1
Order By: Relevance
“…Data from a national survey conducted in the United States showed that 58% of the elderly persons died in hospitals, 22% died in their homes, and 20% died in nursing homes (Weitzen, Teno, Fennell, & Mor, 2003). Among patients with Alzheimer's disease, 40% died at home, 30% died in hospitals, and 30% died in nursing homes (Owen, Goode, & Haley, 2001), while in France, only 36% of those who were followed up by the home care coordinating unit had an in-home death (Chvetzoff et al, 2005). In Israel, only 44% of those who received home hospice services died in their homes (Bentur, Resnizki, & Shnoor, 2005) and in another study, death at home occurred for 80.3% of cancer patients who received home care services in comparison to 20.5% of those without access (Singer, Bachner, Shvartzman, & Carmel, 2005).…”
Section: Sites Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from a national survey conducted in the United States showed that 58% of the elderly persons died in hospitals, 22% died in their homes, and 20% died in nursing homes (Weitzen, Teno, Fennell, & Mor, 2003). Among patients with Alzheimer's disease, 40% died at home, 30% died in hospitals, and 30% died in nursing homes (Owen, Goode, & Haley, 2001), while in France, only 36% of those who were followed up by the home care coordinating unit had an in-home death (Chvetzoff et al, 2005). In Israel, only 44% of those who received home hospice services died in their homes (Bentur, Resnizki, & Shnoor, 2005) and in another study, death at home occurred for 80.3% of cancer patients who received home care services in comparison to 20.5% of those without access (Singer, Bachner, Shvartzman, & Carmel, 2005).…”
Section: Sites Of Deathmentioning
confidence: 99%
“…The probability of death at home among elderly persons using PACE was twice as high as in the general elderly population because of the extensive and intensive services provided by the program (Temkin-Greener & Mukamel, 2002). Greater availability of home hospice providers was also associated with dying at home rather than in a hospital or in an inpatient hospice (Gallo et al, 2001;Singer et al, 2005;Weitzen et al, 2003), as was the availability of a medical oncologist for home visits (Chvetzoff et al, 2005).…”
Section: Downloaded By [Gazi University] At 17:58 03 January 2015mentioning
confidence: 99%
“…Factors associated with home deaths have been identified in some studies 3, 1115. A systematic literature review of place of death for cancer patients grouped these factors as environmental, individual and illness-related 16.…”
Section: Introductionmentioning
confidence: 99%
“…De maniè re plus inté ressante, le nombre de visites à domicile du mé decin traitant ou des infirmiè res semble corré lé audé cè s à domicile [8,18,26] de mê me que l'existence d'un programme de coordination [9,14,[18][19][20]23], mê me si certains auteurs ne confirment pas cette hypothè se [20,23,28]. Dans notre expé rience, qui n'est pas celle d'une é quipe mobile de soins palliatifs mais d'une structure de coordination en oncologie gé né rale, le MOC apparaît comme un é lé ment clé du dispositif, vé ritable pont entre l'oncologue et les soignants du domicile, permettant à chacun de trouver sa place spé cifique tout en contribuant tous ensembles au succè s du projet de soins à domicile [12]. Sa spé cificité d'oncologue rompu par ailleurs à la pratique des soins palliatifs lui permet de coordonner la prise en charge à toutes les phases de maladie.…”
Section: Discussionunclassified